Classification of management tools in small business organizations for developing a sales funnel - E. R. Tolstova; L. V. Silakova (Омский научный вестник: Серия "Общество. История. Современность")
In the modern world, companies that use CRM systems, SMM marketing (digital marketing in social networks), provide this, cause of the demand to build a sales funnel. The main goal is to build an effective sales funnel that will attract customers and increase profits. This study is aimed at selecting a set of services that can help the development of a small business characterized by low revenue volumes, and, as a result, small budgets for promotion, as well as a small number of staff. The article discusses the current problems of small business, CRM systems and services that help promote social networks. The main applied research methods: these are abstraction, generalization, competitive analysis and comparison. The following problems are identified for small businesses: the issue of scaling, the need to automate workflows, collecting feedback and feedback from customers, processing applications, great competition in the market, parallelization of workflows, organization of hierarchy in the workflow. The concept of sales funnels for any type of organization, enterprise, startup, etc. is considered. Common features, stages that should characterize the planned sales funnel are highlighted. A comparison of various services that help in the development and implementation of a marketing strategy is carried out. There are 4 categories of digital services for working with business automation and sales funnel: information systems and technologies that help to design a business model as a whole, create quality management systems, etc.; programs for business modeling, development of working documentation and requirements; CRM systems designed for planning employee tasks and storing customer data; services that help with promotion in social networks. Thanks to them, such tasks as: modeling of the sales funnel, automation of business processes, templates of working scenarios, instructions, regulations for employees, conversion analytics and traffic arbitration are solved. The classification of programs and services that will automate the company’s sales funnel, taking into account the price of the product and its functionality, the combination of which will be optimal for small businesses, is proposed.